Recommendation Dialog System for Selecting the Computer Hardware Configurationconfiguration - Svystun, Oksana; Yurchak, Iryna (Lviv Politechnic Publishing House, 2021)
The development of modern technologies is extremely fast. Every day more and more new and various means appear in the world to improve the quality of life and more. It is not possible for a person to process all this new information on the scale and speed with which this information appears. Everyone has their own preferences and wants to receive and obtain information about certain events or things that they are interested in. This has become one of the most important reasons for creating referral systems. The purpose of developing a recommended dialog system for selecting the computer hardware configuration is to help users choose the computer's hardware characteristics to suit their requirements and needs. This system is suitable for being used by both qualified users in this field, and for users unfamiliar with computer technology. There has been an attempt to analyze the types of recommendation dialog systems and their varieties in the paper. The principle of operation of the recommendation dialog system in the form of a chat bot made on the platform of the messenger Telegram has been considered.
Keywords: recommendation system; dialog system; chat bot; Telegram; computer hardware configuration